ANALISIS PENGARUH SUASANA TOKO TERHADAP KEPUTUSAN PEMBELIAN MELALUI EMOSI KONSUMEN SEBAGAI VARIABLE INTERVENING PADA 7-ELEVEN WILAYAH DEPOK MARGONDA - M. Lutfi Alfian Zauhari (2017)
The design of the shop atmosphere in a retail store, especially on convinience store such as 7 - Eleven is very important. I order to provide the consumer stimulates positive emotions which certainly have an impact on their purchasing decisions. This study was condected to examine the effect of the atmosphere of the store to the consumer purchasing decisions throught emotion 7 - Eleven South Margonda Depok. The population in this study is the consumers who visit 7 - Eleven South Margonda Depok. In determining the sampel size formulas used in this study Roscoe and abtained 100 respondents to be tested. The sampling tehnique used purposive sampling. Data used in this study are primary data, source data obtained from questionnaires. Data analysis method used is path analysis and hypotesis testing using t test and F with 5% confidence level, using SPSS sofwere. The results showed that the atmosphere of the store significant effect on consumer emotions, significant influence on purchasing decisions. This study also showed a significant influence between the atmosphere shop to purchasing decision indrectly through consumer emotions. Similarly, the consumer emotions significantly influence the purchase decision.